Bom dia, Harry Stone: o embaixador de Hollywood no Brasil (1953 – 2000) - Rodrigues, Bruna Carolina de Oliveira (2021)
This dissertation has as its theme Mr. Harry Joe Stone’s life, with greater emphasis on the period he lived in Brazil, from 1953 until his death in 2000. Mr. Stone was a representative of the Motion Picture Association of America (MPAA), an association of leading Hollywood film companies such as Warner Brothers, Fox and MGM. Also called the “Hollywood ambassador”, Stone represented the interests of such companies and he was a great lobbyist, being frequently seen both in the main events of the carioca elite and in the corridors of the Planalto Palace. Given the lack of information gathered about Harry’s hole in Brazil, I defined that the general objective of my research is to understand the trajectory and performance of Mr. Stone in Brazil, from 1953 to 2000. The following specific objectives were established: catalog and build a timeline with the main news about Stone, investigate its actions and its impact, analyzing whether, in fact, we can call him “Enemy of national cinema” - as he was characterized many times. Being Mr.Stone from the United States, the fundamental theorist was composed of works that deal with the relationship between Brazil and the United States (TOTA, 2000, 2014; FONSECA, 1989), works that analyze the power and influence of Hollywood films (SKLAR, 1994; FURHAMMAR, ISAKSSON, 1976) and Brazilian cinema (RAMOS; SCHVARZMAN, 2018). The corpus of sources is mainly composed of news from newspapers and magazines available in digital version by the National Library. Documents made available by Cinemateca Brasileira (SP), Cinemateca do MAM (RJ) and Arquivo Nacional (RJ) were also used, in addition to reports from people who lived with Harry Stone